SENTENCE FRAGMENTS IN SEA TEACHER BLOG WRITING IN ST. PAUL UNIVERSITY SURIGAO, PHILIPPINES - Entika Fani Prastikawati; Beny Arum Setianingsih; Wiyaka (Wiralodra English Journal, 2020)
This study aimed to identify fragments found on online diaries of 6th batch SEA Teacher blog writing in St. Paul University Surigao, Philippine, and to describe the problems faced by 6th batch SEA Teacher participants in writing online diaries. The research design of this study was descriptive qualitative. For collecting data, the researchers used non-interactive techniques by analyzing ten formal online diaries and distributing the questionnaire. The researchers employed three steps for analyzing the data, namely data reduction, data display, and drawing some conclusions. The researchers analyzed ten formal online diaries, the researcher found fragments on seven formal online diaries. The most significant fragment realized was missing verbs (56.52%) followed by missing subject (30.43%), added detail fragment (8.70%), and –ing fragment (4.34%). Whereas, the highest problem faced by 6th batch SEA Teacher participants in writing online diaries was lack of grammar knowledge, time limitation, limited reference, and different language used.